Rural Economic Improvement Strategies by Optimizing The Digital Marketing Application (Case Study: Tirtayasa Village, Serang Regency, Banten Province) - Herlina, Deswita; Mangara, Togi Haidat; Siahaan, Olindayanti; Simanjuntak, Togi Marito (EQUATOR SINAR AKADEMIA, 2025)
Sultan Ageng Tirtayasa University (Untirta) is actively involved in community service, one of which takes place in Tirtayasa Village. The village still has limited infrastructure and a demographic profile largely consisting of farmers and daily laborers. Although there have been efforts to develop micro, small, and medium enterprises (MSMEs), local potential—such as culinary products—has not been fully optimized. A major challenge is the community’s lack of basic knowledge and skills in using digital platforms such as social media, online marketplaces, and digital marketing strategies. To address this issue, a digital marketing training program was conducted to improve the community’s ability to promote their products online and to encourage creativity in developing the village’s flagship products. The program was carried out in four stages: preparation, implementation, evaluation, and reporting. The USG (Urgency, Seriousness, and Growth) analysis was used to identify key problems. The results show that the training not only successfully transferred technical knowledge, but also inspired participants to adopt more innovative approaches in developing their businesses.